2016
DOI: 10.18006/2016.4(issue6).631.636
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic and mineral fertilizers on chemical and biochemical compounds content in tomato (Solanum lycopersicum) var. Mongal F1

Abstract: The concentration of secondary metabolites can be influenced qualitatively and quantitatively by ecological factors and farming practices. The purpose of this study was to determine the impact of organic and mineral fertilization on physical characteristics and the content of chemical and biochemical compounds of the fruits of the tomato var. Mongal F1. Physical, chemical and biochemical characterizations of tomato samples were carried out from samples collected from control, organic and mineral fertilized pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
3
5
1
Order By: Relevance
“…These values are relatively similar to those reported by various researchers in previously conducted studies (Eivazi et al, 2013;Dabire et al, 2016;Youssef & Eissa, 2016 Dabire et al (2016) those who found that TA value was higher in plants treated with organic compounds compared to plants treated with either mineral fertilizers or control. Generally, the TA value of Asala F1 tomato in this study is relatively higher than the value reported by Youssef & Eissa (2016) who found that the TA value of tomato (Egyptian local variety) ranged from 0.22-0.39%, but is lower compared to the TA value (7.72 to 8.81%) of Mongal F1 tomato reported by Dabire et al (2016). These variations in TA value could be justified based on the different tomato varieties tested (Dabire et al, 2016).…”
Section: Fruit Quality Aspectssupporting
confidence: 91%
See 1 more Smart Citation
“…These values are relatively similar to those reported by various researchers in previously conducted studies (Eivazi et al, 2013;Dabire et al, 2016;Youssef & Eissa, 2016 Dabire et al (2016) those who found that TA value was higher in plants treated with organic compounds compared to plants treated with either mineral fertilizers or control. Generally, the TA value of Asala F1 tomato in this study is relatively higher than the value reported by Youssef & Eissa (2016) who found that the TA value of tomato (Egyptian local variety) ranged from 0.22-0.39%, but is lower compared to the TA value (7.72 to 8.81%) of Mongal F1 tomato reported by Dabire et al (2016). These variations in TA value could be justified based on the different tomato varieties tested (Dabire et al, 2016).…”
Section: Fruit Quality Aspectssupporting
confidence: 91%
“…Generally, the TA value of Asala F1 tomato in this study is relatively higher than the value reported by Youssef & Eissa (2016) who found that the TA value of tomato (Egyptian local variety) ranged from 0.22-0.39%, but is lower compared to the TA value (7.72 to 8.81%) of Mongal F1 tomato reported by Dabire et al (2016). These variations in TA value could be justified based on the different tomato varieties tested (Dabire et al, 2016). On the other hand, compost types enriched with moderate and higher rates of sheep manure (C3, C4, and C5) increased juice volume in comparison with C1 and C2 compost types (Table 5).…”
Section: Fruit Quality Aspectscontrasting
confidence: 75%
“…Despite the importance of the tomato fruit in Burkina Faso, to date very few published studies were done on the nutritional and health characteristics of tomato in Burkina Faso. Most of the researches done are oriented to agronomy practices [14]. Therefore the aim of the present study was to determine the morphological and physicochemical characteristics, the nutritional composition and the levels of trace metals of tomato Mongal F1 for technological and nutritional interest.…”
Section: Introductionmentioning
confidence: 98%
“…The same source states that, soils rich in humus with high biological activity can positively modify the concentration and the combination of antioxidants in harvested fruits and vegetables, compared to soils that are regularly fumigated and extensively chemical fertilized, and which have a generally lower bioactivity [41]. It could be argued that the ability of organic farming practices to increase the antioxidant content of fruits and vegetables would come from the use of organic fertilizers and pesticides, which are very rich in organic and probably other agro-ecological parameters could explain the increase of antioxidant content in organic farming according to many authors, Dakéné, et al [42]; Sereme, et al [43]; Dabire, et al [44].…”
Section: Cultural Practices and Influence On The Antioxidant Content mentioning
confidence: 99%